QSPR graph model to explore physicochemical properties of potential antiviral drugs of dengue disease through novel coloring-based topological indices - Yogalakshmi, C.; Balamurugan, B. J. (Frontiers in Chemistry, 2025)
Dengue is a viral disease transmitted to humans through mosquito bites. Researchers have investigated various drugs with potential antiviral properties against it. Some of the promising antiviral drugs include UV-4B (N-9-methoxynonyl-1-deoxynojirimycin), Lycorine, ST-148, 4-HPR, Silymarin, Baicalein, Quercetin, Naringenin, Nelfinavir, Ivermectin, Mosnodenvir (JNJ-1802), NITD-688, Metoclopramide, JNJ-A07 and Betulinic acid. The chemical structure of a drug can be modelled as an isomorphic molecular graph G(V,E), considering the atoms as the vertex set V(G) and the bonds between the pair of atoms as the edge set E(G). Graph coloring and topological indices serve as a powerful tools for analyzing the isomorphic molecular graph, providing the structural characterization and computational studies. In this article, two types of coloring-based topological indices viz., chromatic topological indices and induced color-based topological indices, are introduced. Linear regression is employed in the QSPR(Quantitative Structure Property Relationship) analysis to examine the dengue antivirals through the computed topological indices of the aforementioned drugs. The results of the QSPR analysis reveal that the induced color-based indices provide better predictions of the physicochemical properties of dengue-treating drugs.